2024
DOI: 10.3389/fimmu.2023.1299792
|View full text |Cite|
|
Sign up to set email alerts
|

Urokinase-type plasminogen activator and plasminogen activator inhibitor-1 complex as a serum biomarker for COVID-19

Tetiana Yatsenko,
Ricardo Rios,
Tatiane Nogueira
et al.

Abstract: Patients with coronavirus disease-2019 (COVID-19) have an increased risk of thrombosis and acute respiratory distress syndrome (ARDS). Thrombosis is often attributed to increases in plasminogen activator inhibitor-1 (PAI-1) and a shut-down of fibrinolysis (blood clot dissolution). Decreased urokinase-type plasminogen activator (uPA), a protease necessary for cell-associated plasmin generation, and increased tissue-type plasminogen activator (tPA) and PAI-1 levels have been reported in COVID-19 patients. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Our data revealed elevated levels of uPA in non-survivors and an adjusted HR of 4.2 (95% CI: 1.5–11.7, p = 0.006) for mortality. In contrast, Yatsenko Tetiana et al [ 38 ] reported decreased levels of uPA in patients with COVID-19. These differences may be due to the severity of the disease and sample size.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our data revealed elevated levels of uPA in non-survivors and an adjusted HR of 4.2 (95% CI: 1.5–11.7, p = 0.006) for mortality. In contrast, Yatsenko Tetiana et al [ 38 ] reported decreased levels of uPA in patients with COVID-19. These differences may be due to the severity of the disease and sample size.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, the sample from Yatsenko et al shows parameters beyond the median of our population, which can indicate the phases of COVID-19. While they have uncomplicated and complicated COVID-19 cases, ours were all severely affected, so as to further draw a distinction between the two groups of patients [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%